Khazanah Studi Kitab Tafsir di Indonesia (Kajian Terhadap Kitab Tafsir Ringkas Kementerian Agama Republik Indonesia) - Muhammad Faisal (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2019)
Discussion of interpretation is an important thing in the study of the Qur’an. Understanding the Qur'an is by interpreting the Qur’an. Ulama have tried from time to time to compose the Qur'anic commentary. But for some people it is assumed that many of the interpretations written by the ulama are not easy for every community to digest even more so for the people of Indonesia. There are several things that make the interpretation book difficult to digest by some people, one of which is a complicated style of language added with an understanding of Arabic that is lacking for some Indonesian people, this becomes a problem for the community to understand the interpretation of the Qur’an. The Indonesian Ministry of Religion through the Institute of the Qur'an has tried to solve this problem by composing two works, namely the Qur'an and its translation and the Qur'an and its interpretation. But both of them are still considered inadequate on the grounds that the work of the Qur'an and the Translation are still considered too narrow, the discussion is only as a language transfer. Whereas the Qur'anic work and its interpretation are very broad. Therefore it is presented in brief interpretation as an effort to mediate it. The method and systematics of writing this book are adjusted so that it can be understood by all levels of society. This explanation uses a descriptive-analysis approach. The result is that the explanations in this concise interpretation use methods that are easy to understand by the people of Indonesia. DOI: https://doi.org/10.5281/zenodo.3236464